Architecture of the Saccharomyces cerevisiae SAGA transcription coactivator complex - Han, Yan (EMBO J, 2014)
The conserved transcription coactivator SAGA is comprised of several modules that are involved in activator binding, TBP binding, histone acetylation (HAT) and deubiquitination (DUB). Crosslinking and mass spectrometry, together with genetic and biochemical analyses, were used to determine the molecular architecture of the SAGA-TBP complex. We find that the SAGA Taf and Taf-like subunits form a TFIID-like core complex at the center of SAGA that makes extensive interactions with all other SAGA modules. SAGA-TBP binding involves a network of interactions between subunits Spt3, Spt8, Spt20, and Spt7. The HAT and DUB modules are in close proximity, and the DUB module modestly stimulates HAT function. The large activator-binding subunit Tra1 primarily connects to the TFIID-like core via its FAT domain. These combined results were used to derive a model for the arrangement of the SAGA subunits and its interactions with TBP. Our results provide new insight into SAGA function in gene regulation, its structural similarity with TFIID, and functional interactions between the SAGA modules.